Milvago chimango corrective osteotomy of an angular deformation of tibia-tarsal bone (Veterinary Science, 2017)
The authors report the result of the correction of an angular deformity of the tibiotarso bone of a Milvago chimango. An osteotomy was performed in the place of the deviation followed by a subsequent stabilization of the limb with an external skeletal fixator whose central bar was made of metacrilate. The surgical evaluation of the osteotomy determined the removal of the fixator 30 days after surgery. The osteotomy corrected the bone deviation and allowed the recovery of the seizing ability ofthe claw